REMEMBERING: SPORTS AND EDUCATION / SPORTS AND CULTURE (Fiep Bulletin - online, 2012)
SPORTS AND EDUCATIONDespite the fact that there are sports facilities in educational institutions, sports are still notincluded in the very life of the educative community. The author suggests reciprocal opening andinterpenetration between education and sport. Radical changes are needed in the educational systemorganization, aiming at a multidimensional model. It is also necessary that sport undergoes a deepchange, through a double process of returning to its sources and continuously reinventing itself. Itshould not be so focused on sports shows, as it is now due to market, national and political interests.Sports and education must work together, enriching and reinforcing each other mutually with theirexperiences and resources. SPORTS AND CULTUREBoth sports and culture contribute to enrich human heritage. Nowadays, sports are the mostcommon form of leisure, and because they are more appealing to masses than culture, they play therole of culture. But, due to sociological, ethical and esthetic aspects, sport is a form of culture whichhas not yet reached the formal expression that is associated with the latter. According to the author,there may always be a parallelism between sports and culture, but never an identity. We should try tounite body and mind, the two sides of the same humanism. It is absolutely necessary that sports andculture converge and understand each other.
Keywords: sports; education; humanistic values; olympic ideals; cultures; leisure; competition